Evaluation of the implementation and effectiveness of a multifactorial intervention strategy for safe patient handling and movement in the healthcare sector: a study protocol of a cluster randomised controlled trial. Issue 2 (3rd February 2023) - Wåhlin, Charlotte; Buck, Sebastian; Sandqvist, Jan; Enthoven, Paul; Fock, Jenni; Andreassen, Maria; Strid, Emma Nilsing
Abstract : Introduction: Healthcare workers with physically demanding work tasks, such as patient handling and movement (PHM), are at high risk of musculoskeletal disorders. To facilitate safe PHM and prevent musculoskeletal disorders, a combination of workplace interventions, including risk assessments, is needed. The aim of this study is to implement and evaluate a multifactorial intervention strategy for safe PHM and compare it with a single intervention strategy. Methods and analysis: This cluster randomised controlled trial will compare a multifactorial intervention strategy with a single intervention strategy for safe PHM in workplaces in the Swedish regional and municipal healthcare systems. At least twelve healthcare units will be recruited. Care units belonging to arm A will receive: (1) guidelines for PHM, (2) training modules, (3) risk assessment with TilThermometer, (4) risk assessment with Downtown Fall Risk Index and (5) work environment mapping. Care units belonging to Arm B will receive interventions (1) and (5). The two strategies will be evaluated with regards to (1) the primary outcome of the applied strategies' intervention effectiveness (safety climate in relation to aspects of PHM) and (2) the primary implementation outcome (acceptability, appropriateness and feasibility). This study will also explore the implementation process and intervention fidelity, examine the influence of contextual factors and investigate participants' experiences of working with strategies for safe PHM. A mix of quantitative and qualitative methods will be used. The data collection is based on questionnaires, interviews and field notes of contextual factors. Ethics and dissemination: The study is approved by the Swedish national ethical board (Dnr 2021–00578). Study results will be published in peer-reviewed journals, presented at conferences and distributed on social media. A lay summary and dissemination strategy will be codesigned with a reference group and participating healthcare units. Trial registration number: NCT05276180 .